Pengaruh Perceived Ease of Use, Brand Image, Word of Mouth, Nilai Pelanggan terhadap Keputusan Penggunaan Layanan Jasa serta Dampaknya terhadap Loyalitas - Angelina Fitria Rina Sari; Steven Lim (Widya Manajemen, 2022)
This study wants to prove the effect of each variable, namely perceived ease of use, brand image, word of mouth, and customer value which have a positive effect on customer loyalty, where the decision to use services becomes an intervening variable. Based on previous research and related to the supporting theory put forward by experts using the SPSS program as a statistical data processing tool. This type of research is associative research. In this study, researchers used a nonprobability sampling technique because the researcher did not know the total number of members of the population under study. While the sampling technique used in this study was accidental sampling. While the population is all Maxim online transportation users in Pontianak City, and the sample is 100 Maxim online transportation users in Pontianak City, with data analysis techniques using path analysis. Based on data processing using path analysis, it is proven that perceived ease of use, brand image, word of mouth has no positive effect on service use decisions, while customer value and service user decisions also have a positive and significant effect on loyalty with service use decisions. services as an intervening variable.